Protection Against Arthritis by the Parasitic Worm Product ES-62, and Its Drug-Like Small Molecule Analogues, Is Associated With Inhibition of Osteoclastogenesis - Doonan, James; Lumb, Felicity E.; Pineda, Miguel A.; Tarafdar, Anuradha; Crowe, Jenny; Khan, Aneesah M.; Suckling, Colin J.; Harnett, Margaret M.; Harnett, William (Frontiers in Immunology, 2018)
The immunomodulatory actions of parasitic helminth excretory-secretory (ES) products that serendipitously protect against development of chronic inflammatory disorders are well established: however, knowledge of the interaction between ES products and the host musculoskeletal system in such diseases is limited. In this study, we have focused on ES-62, a glycoprotein secreted by the rodent filarial nematode Acanthocheilonema viteae that is immunomodulatory by virtue of covalently attached phosphorylcholine (PC) moieties, and also two synthetic drug-like PC-based small molecule analogues (SMAs) that mimic ES-62’s immunomodulatory activity. We have previously shown that each of these molecules prevents development of pathology in collagen-induced arthritis (CIA), a model of the musculoskeletal disease, rheumatoid arthritis (RA) and reflecting this, we now report that ES-62 and its SMAs, modify bone remodeling by altering bone marrow progenitors and thus impacting on osteoclastogenesis. Consistent with this, we find that these molecules inhibit functional osteoclast differentiation in vitro. Furthermore, this appears to be achieved by induction of anti-oxidant response gene expression, thereby resulting in reduction of the reactive oxygen species production that is necessary for the increased osteoclastogenesis witnessed in musculoskeletal diseases like RA.